2009
DOI: 10.1007/s10815-009-9356-0
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification of human early cavitating and deflated expanded blastocysts: clinical outcome of 474 cycles

Abstract: Purpose The present study was undertaken to evaluate and compare the post thaw survival, implantation and pregnancy rates of vitrified human early cavitating blastocysts with deflated expanded blastocysts. Material and methods Supernumerary blastocysts were vitrified in 30% ethylene glycol-dimethyl sulphoxide based solution using cryoloop. Fully expanded blastocysts were deflated by gentle aspiration of the blastocoelic fluid using a micromanipulator until the cavity collapses prior to vitrification. Results O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…An even higher post-thawing survival rate could be obtained by artificially collapsing blastocoels before vitrifying (Hiraoka et al, 2004). The consistently high postthawing survival rate and the similarity between vitrified embryos and nonvitrified embryos, in terms of their respective implantation rates and pregnancy rates, have been reported repeatedly (Mukaida et al, 2003;Hiraoka et al, 2004;Huang et al, 2005;Isachenko et al, 2007;Kartberg et al, 2008;Raju et al, 2009;Wennerholm et al, 2009).…”
Section: Human-assisted Reproductive Technologiesmentioning
confidence: 91%
“…An even higher post-thawing survival rate could be obtained by artificially collapsing blastocoels before vitrifying (Hiraoka et al, 2004). The consistently high postthawing survival rate and the similarity between vitrified embryos and nonvitrified embryos, in terms of their respective implantation rates and pregnancy rates, have been reported repeatedly (Mukaida et al, 2003;Hiraoka et al, 2004;Huang et al, 2005;Isachenko et al, 2007;Kartberg et al, 2008;Raju et al, 2009;Wennerholm et al, 2009).…”
Section: Human-assisted Reproductive Technologiesmentioning
confidence: 91%
“…Blastocysts are usually considered as pre-implantation embryos which have passed the genomic activation step and have a greater developmental potential [1].…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by human morula and early blastocysts having improved survival rates compared to fully expanded blastocysts after vitrification, however, when the cavity of expanded blastocysts underwent artificial shrinkage, survival rates were equivocal [9]. A further study demonstrated vitrification of early blastocysts resulted in improved survival compared to artificially collapsed expanded blastocysts while implantation and pregnancy rates were the same [30]. Overall the conclusion from these studies is that the morula/early blastocyst may be the best stage for cryopreservation as the embryo is better equipped to counteract osmotic changes, while the lack of the large fluid filled cavity circumvents the need to extended periods of exposure to cryoprotectants or artificial cavity collapse.…”
Section: Discussionmentioning
confidence: 99%